Advances in neurexin studies and the emerging role of neurexin-2 in autism spectrum disorder - Khoja, Sheraz; Haile, Mulatwa T.; Chen, Lulu Y. (Frontiers in Molecular Neuroscience, 2023)
Over the past 3 decades, the prevalence of autism spectrum disorder has increased globally from 20 million to 28 million cases making ASD the fastest-growing developmental disability in the world. Neurexins (Nrxns in mice and NRXNs in humans) are a family of presynaptic cell adhesion molecules that have been previously implicated in ASD, as evidenced by genetic mutations in the clinical population. Nrxns function as context-dependent specifiers of synapse properties and critical modulators for maintaining the excitatory. inhibitory transmission (E/I balance). Disrupted E/I balance has long been established as a hallmark of ASD making Nrxns excellent starting points for understanding the etiology of ASD. Herein, we review NRXN mutations that have been discovered in ASD patients. Further, we discuss synaptic mechanisms underlying the aberrant neurotransmission and behavioral deficits observed in different in Nrxn mutant mouse models, with focus on recent discoveries in the previously overlooked Nrxn, Nrxn2. Hence, the aim of this review is to provide a summary of new synaptic insights into the molecular underpinnings of ASD.